Government expenditures and economic growth: eidence from Malaysia / Rohaiza Kamis, Hairul Nizwan Abd Majid and Nuraida Idora M Ramlee - Kamis, Rohaiza; Abd Majid, Hairul Nizwan; M Ramlee, Nuraida Idora (Research Management Centre (RMC), 2020)
This paper aims to empirically analyze the relationship between government expenditures and economic growth in Malaysia from 1987 to 2016. This study uses the time series data in identifying the economic growth determinants in Malaysia. The Multiple Linear Regression (MLR) is used to establish the relationship between government expenditure which are education expenditure, health expenditure, defense and security expenditure, and social services expenditure towards the economic growth in Malaysia. The findings for this study indicate all the independent variables have a significant relationship towards economic growth in Malaysia where the health expenditure is the most influenced government expenditure component towards the economic growth in Malaysia. These findings may give some overview of policy implications to the policymakers on optimising the effects of government expenditure on economic development.